KEANEKARAGAMAN ARTHROPODA PADA PERTANAMAN CENGKEH (Syzygium aromaticum L.) DENGAN KETINGGIAN BERBEDA DI DESA ONCONE RAYA KECAMATAN TINOMBO SELATAN - Fitriyana, Fitriyana; Toana, Moh. Hibban; Nasir, Burhanuddin (AGROTEKBIS, 2018)
This research is aimed to study the diversity of Arthropod with different altitude. The research was conducted on farmers' clove plantation in Oncone Raya Village, South Tinombo Subdistrict, ParigiMoutong. Arthropod samples were identified at the Plant Disease Pest Laboratory, Faculty of Agriculture, Tadulako University, from May to July 2016. This study      used two treatments with different heights of 640meters (m) above sea level (asl) and 1,700 m asl, using two trap techniques ie traps Traps and the trap of malease, with sampling 8 times. Based      on the results of observations dilapang showed that the number of individuals most abundant         in the lowlands 640m asl 1073 tail, and at least the number of individuals in the plateau           1700m asl 512 tail. With the highest diversity index found on the plateau 1,700 m asl 2.73, with a fairness index of 0.05 for trap trap traps, and for trapping device the malease trap diversity index value is 2.27, the fairness index is 0.97, with the Index Value Similarity 4.69%. As for the lowland diversity index, the lower incidence of occurrence index (H') was 2.68 individuals, (E) 0.04 for trap trap traps, and for male trap traps (H') 2.60, (E ) 0.94, with the value of the similarity index          (SI) 3.17%. Diversity index in moderate category or in other words ecosystem condition in       stable condition.